The contact stress distribution in the receding contact of an elastic layer with a rigid base. (1st March 2022) - Adams, George G.
Abstract: The receding contact between a semi-infinite elastic strip and a flat rigid base is considered. This problem is analyzed using linear elasticity with a shear force and a bending moment applied to its end and with frictionless contact with the base. The solutions for a separately applied shear force and a bending moment are determined in which adhesion with the rigid base is allowed for each problem. However the receding contact does not allow adhesion and so the superposed problem cancels the stress singularities resulting in a bounded contact pressure distribution. This distribution becomes independent of the out-of-contact length to thickness ratio. The maximum contact pressure is shown to be about one-half of that obtained by using structural mechanics theory with shear deformation included (Timoshenko beam theory). Furthermore the center of pressure of this distribution is at a distance from the contact boundary comparable to the thickness of the layer. Thus the condition of zero bending moment used in classical beam/plate theories should be modified accordingly.